(untitled) - Schneider, T. (London, 2000)
This book offers an understanding from the phase transition point of view, surveys and identifies thermal and quantum fluctuation effects, identifies material-independent universal properties and provides constraints for the microscopic description of the various phenomena. The text is presented in a format suitable for use in a graduate level course.
Keywords: Semiconductors,Siêu dẫn nhiệt độ cao,High temperature superconductivity,Chất bán dẫn